Kinematics analysis: Number of trials necessary to achieve performance stability during soccer instep kicking - Amiri-Khorasani, M. (De Gruyter Open, 2010)
The purpose of tins study was to investigate the stability of kinematics responses related to stretch shortening cycle (SSC) during 10 consecutive soccer instep kicks The kicking motions of dominant legs were captured from five experienced adult male soccer players (body height 184 60 +/- 4 49 cm, body mass 80 +/- 4 24 kg, age 25 60 +/- 1 14 years) using a three-dimensional infra-red high speed camera at 200 Hz Sonic important kinematic parameters include eccentric angular velocity (AVe), concentric angular velocity (AVc), duration of eccentric (Te), and duration of concentric (Tc) at forward and impact phases selected to analyses The AVe result of the sixth kick, relative to the first kick, was significantly lower when compared to the other kicks (with p <= 0 001.) The AVc result of the fifth kick, relative to the first kick, was significantly lower when compared to the other kicks (with p <= 0 001) The Te result of the fourth kick, relative to the first kick, was significantly lower when compared to the other kicks (with p <= 0 011) The Tc result of the Nth kick, relative to the first kick, was significantly lower when compared to the other kicks (p <= 0 029) We concluded that 5 consecutive kicks arc adequate to achieve high kinematic responses related to SSC